Socio-Cultural Aspect Of Sustainable Tourism In Indonesia: Case Study In Banyumas Regency (Journal of Namibian Studies : History Politics Culture, 2023)
Purpose – Banyumas Regency has many potential tourism destination spot that is not properly develop even though tourism contributed 90% of Banyumas’s regional income. The aim of this study is to investigate the potential of underdeveloped socio-cultural tourism in Banyumas Regency and to find whether the socio-cultural aspects of sustainable tourism principles have been implemented in tourism development program of Banyumas.Design/Methodology – Qualitative methods were used to enable authors to probe deeper into the topics and draw thorough conclusion based on the respondents’ answers. Authors will use data collected through several interviews with the local artist as primary data while data collected from Banyumas Regency Tourism Office will be used as secondary data to support the author's arguments.Findings -. Authors finds that socio-cultural aspects such as cultural wealth is the dominant principles of sustainable tourism in Banyumas due to its geographically unique position. Local government should maximize this potential for further development of socio-cultural tourism while adhering to sustainable principles.Originality - Practical implication of this study is the local government should gain important insight of what tourism aspect they need to improve to make Banyumas a better tourist destination.